2015
DOI: 10.1128/genomea.00154-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Salmonella enterica Serovar Typhimurium Myophage Mushroom

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) is a leading cause of foodborne illness worldwide. Over the past two decades, strains resistant to antibiotics have begun to emerge, highlighting the need for alternative treatment strategies such as bacteriophage therapy. Here, we present the complete genome of Mushroom, an S. Typhimurium myophage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…A comparison using the BLASTn algorithm of these phage genomes showed that the WHR phage’s top BLAST hit is a phage previously sequenced, named Salmonella virus Mushroom, with GenBank acc: KP143762.1 [62], and the NHR phage’s first BLAST result is Salmonella phage FelixO1, with GenBank acc: AF320576.1 [61]. A BLASTn comparison between WHR and NHR phages showed 97% nucleotide identity, shared among their genomes.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison using the BLASTn algorithm of these phage genomes showed that the WHR phage’s top BLAST hit is a phage previously sequenced, named Salmonella virus Mushroom, with GenBank acc: KP143762.1 [62], and the NHR phage’s first BLAST result is Salmonella phage FelixO1, with GenBank acc: AF320576.1 [61]. A BLASTn comparison between WHR and NHR phages showed 97% nucleotide identity, shared among their genomes.…”
Section: Resultsmentioning
confidence: 99%
“…The BLASTn results showed that the closest neighbors of phages VSe11 and VSe102 are the Salmonella phages Mushroom (GenBank accession no. KP143762) ( 13 ), SPT-1 (JX181822), and Si3 (KY626162). All of them encode core proteins inherent to Felix O1-like phages of the family Myoviridae subfamily Ounavirinae ( 14 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…They are classified as members of the subfamily Ounavirinae [12]. The FO1-like Salmonella phages Mushroom and FO1a are components of commercially available phage cocktails (IntestiPhage™ and PhageGuard S™, respectively) [13, 14]. GJ1-like phages are also virulent myoviruses.…”
Section: Introductionmentioning
confidence: 99%